Social and Economic Aspects of Soil Conservation in the Machkund Basin - Maddruddin, S. M. (Journal of Soil and Water Conservation, 2022)
The success of soil and water conservation measures depend upon the cooperation and active participation of the native inhabitants of the watershed in which the works are to be carried out. We must attempt to win the interest, the mind, the heart and hands of the local people. The spirit of the people must be evoked and the departments should do for the people what is best in a manner most agreeable to the inhabitants. The understanding of the traditional attitudes of the community is essential. The tribals inhabiting the Machkund Basin are superstitious and hold tenaciously to the views and attitudes which they have inherited by tradition from their forefathers. It is the realisation of this background and a sympathetic approach to blend with t heir traditional beliefs the technical aspects of soil conservation that will help in the ultimate success of the soil and water conservation works. To attempt to bring in new methods which do not have a bearing on all that the local people believe to be important in their fields would be to court a complete lack of confidence. It would therefore be clear that we should understand the socio-economic conditions and aptitudes of the people and educate them on Proper lines by constant touch and by demons-tration in the field to see the results for themselves. This aspect of soil conservation has to be paid much attention in Machkund Basin.